Management and outcomes of chest pain telemedicine visits in a cardiology clinic during the COVID-19 pandemic. Issue 3 (4th May 2023) - Adams, Kadilee; Wahab, Laith; Rhodehouse, Bryce C.; Acton, Tayler J.; Yakubik, Taylor B.; Stafford, Joseph A.; Costa, Steven M.
Abstract: Background: Beginning in March 2020, the COVID-19 pandemic forced many outpatient chest pain evaluations to be performed via telemedicine. The purpose of this study was to examine the impact of telemedicine on management and outcomes of patients who presented with chest pain. Methods: This retrospective chart review study included 771 unique patients, age >18 years, who were seen face-to-face in cardiology clinic visits from March 2019 through September 2019 with an encounter diagnosis of chest pain or angina, compared with 172 unique patients of age >18 who were seen via telehealth visit from March 2020 through September 2020. Data were extracted on patients' clinical outcomes up to 1 year after the initial visit, including emergency department visit or hospital admission for chest pain, any hospital admission, additional diagnostic testing, revascularization, and death (cardiovascular or any). Results: The telehealth group had higher rates of emergency department visits (19.2% vs 11.7%, P =  0.008), hospital admissions for chest pain (16.9% vs 10.5%, P =  0.019), as well as all hospital admissions (36.1% vs 28.2%, P =  0.04) compared with the face-to-face group. More patients in the face-to-face group received a stress test (41.1% vs 21.5% for the telehealth group; P <  0.001). There were no other statistically significant differences for diagnostic evaluations, revascularization, or death. Conclusion: Our findings suggest that in-person evaluation for chest pain may aid in reducing the number of emergency department visits and hospital admissions when compared to telehealth evaluation.